COMMUNICATION STRATEGY OF ISLAMIC EXTENSION IN THE INDONESIAN-MALAYSIA BORDER REGION - Halim Setiawan (UIN Sunan Gunung Djati Bandung, 2019)
Paloh District has its characteristics or characteristics that are different from other border areas. The culture of the people is different, the level of education is different so that the messages delivered are also different da'wah. The da'wah challenges faced by Non Civil Servant Islamic Religious Instructors are also different. The purpose of this study was to explain the choice of strategy and message design of Non-PNS Islamic Extension Instructors in Paloh District, Sambas Regency. Research is based on a macro cognitive theory with naturalistic and qualitative paradigms. The process of delivering da'wah messages in the guidance and counselling activities of Islam uses the choice of strategy and message design. Submission of da'wah messages carried out in three forms of counselling activities, namely the Al-Quran Education Park (TPQ), Mosque Youth and Taklim Assembly. The choice of a strategy used is by reading, memorizing and lecturing. While the message design used is informative and persuasive with the type of message of faith, worship and morals